Expression of paxillin in laryngeal squamous cell carcinoma and its prognostic value - Li, Lianqing (Int J Clin Exp Pathol, 2015)
Paxillin (PXN) gene has been reported to act as an oncogene in many malignancies and play important roles in the development of human carcinomas. However, the relationship between the expression of PXN and clinicopathological characteristics in human laryngeal carcinoma remains unclear. This study aimed to examine the expression of PXN, and to evaluate the clinical significance of its expression in human laryngeal squamous cell carcinoma (LSCC). Real-time quantitative PCR (qRT-PCR), Western blotting and immunohistochemistry were performed to analyze the expression of PXN in LSCC tissues and corresponding paracancerous normal tissues. Kaplan-Meier survival and Cox regression analyses were performed to evaluate the prognosis of patients with LSCC. The expression of PXN was significantly higher in LSCC than in matched paracancerous normal tissues. Immunohistochemical analysis was performed in human LSCC samples and the data were correlated with clinicopathologic features. Levels of PXN in LSCC were related to histopathological grade (P = 0.016), Lymph node metastasis (P = 0.029) and TNM stage (P < 0.001). Kaplan-Meier analysis revealed that survival curves of the overall survival of patients with high PXN expression was significantly worse than that of low PXN expression (P = 0.035). Cox regression analysis revealed that PXN expression level was an independent prognostic factor of the overall survival rate of patients with LSCC (P = 0.002). These findings suggest that PXN expression has potential use as a novel biomarker of LSCC patients and may serve as an independent predictive factor for prognosis of LSCC patients.